2014
DOI: 10.1590/s0100-736x2014000800001
|View full text |Cite
|
Sign up to set email alerts
|

Severe diarrhea outbreak in beef calves (Bos indicus) caused by G6P[11], an emergent genotype of bovine rotavirus group A

Abstract: The episodes of diarrhea caused by neonatal bovine rotavirus group A (BoRVA) constitute one of the major health problems in the calf rearing worldwide. The main G (VP7) and P (VP4) genotypes of BoRVA strains involved in the etiology of diarrhea in calves are G6P[1], G10P[11], G6P[5], and G8P[1]. However, less frequently, other G and P genotypes have been described in BoRVA strains identified in diarrheic fecal samples of calves. This study describes the identification and molecular characterization of an emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 41 publications
1
22
1
Order By: Relevance
“…Alkan et al (2010) reported that the G6P[11] lineage found in Turkey formed a unique G6 lineage with only 90.1% amino acid identity to the G6 strain NCDV found in the vaccines. Medeiros et al (2014a) also reported an outbreak of diarrhea in beef calves in Brazil caused by a G6P[11] distant from the most common lineages of RVA strains G6P[1] and G6P [5]. As the strain found in the vaccinated herd of the present study showed a nucleotide sequence identity of 91.2% to the Fig.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Alkan et al (2010) reported that the G6P[11] lineage found in Turkey formed a unique G6 lineage with only 90.1% amino acid identity to the G6 strain NCDV found in the vaccines. Medeiros et al (2014a) also reported an outbreak of diarrhea in beef calves in Brazil caused by a G6P[11] distant from the most common lineages of RVA strains G6P[1] and G6P [5]. As the strain found in the vaccinated herd of the present study showed a nucleotide sequence identity of 91.2% to the Fig.…”
Section: Discussionsupporting
confidence: 64%
“…The strain found in the vaccinated herd (G6P[11]) was different from the strain of the non-vaccinated herd (G6P[5]), and none of these strains were present in the commercial vaccines available by the time of the experiment. In Brazil, G6P [11] has been incriminated as a cause of a diarrhea outbreak in a beef herd (Medeiros et al 2014a), although there are also reports of its occurrence as the most common genotypic combination in some states of country (Silva et al 2012). In Ireland, G6P[11] is reported as a low prevalence genotypic combination found especially in dairy herds (Collins et al 2014), while in Turkey, Alkan et al (2010) reported a high prevalence of this genotype in either unvaccinated herds and in herds immunized against G6P [1].…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of RVA have already been described globally [12,[23][24][25][26][27][28][29][30], in Brazil, the occurrence, diversity and role of rotavirus in these animals are still poorly studied, considering the large number of present species [4,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, epidemiological studies conducted to date have shown that, in calves, bovine rotavirus A (BoRVA) is the virus most commonly associated with neonatal diarrhea (Alfieri et al 2004, Silva et al 2012, Medeiros et al 2014. Rotaviruses belong to the Reoviridae family and have a triple-layered icosahedral protein capsid.…”
Section: Introductionmentioning
confidence: 99%
“…Among the P genotypes, P[1], P[5] and P [11] are found in RVA strains of bovine origin. The G and P genotype combinations most commonly found in bovine RVA strains are G6P (Alfieri et al 2004, Caruzo et al 2010, Martella et al 2010, Freitas et al 2011, Badaracco et al 2012, Papp et al 2013, Collins et al 2014, Medeiros et al 2014. RVs cause malabsorption and toxin-mediated secretory diarrhea, especially in calves less than 3 weeks old (Foster & Smith 2009).…”
Section: Introductionmentioning
confidence: 99%